Imidacloprid poisoning case series: potential for liver injury - C. Sriapha (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Introduction: Imidacloprid is a commonly used neonicotinoid insecticide in Thailand. Limited reports suggest it may be associated with liver injury. Case series: A retrospective poison center case series identified 128 cases of imidacloprid ingestion from 2010–2016, of which four developed liver injury. Results: Three patients ingested soluble liquid concentrates and one ingested water-dispersible granules of imidacloprid. The estimated doses of ingestion ranged from 2–35 g. One patient developed cholestatic liver injury, two developed hepatocellular liver injury, and the remaining patient, who ingested the highest dose, developed a mixed pattern of liver injury. Median onset of liver injury was 5.5 days. Discussion: In prior case reports and animal studies, these cases suggest imidacloprid toxicity is associated with liver injury that may be delayed. This is consistent with our finding. The cases also demonstrated a possible dose-response relationship of imidacloprid ingestion with severity and type of liver injury. All findings suggested that imidacloprid might contribute to liver injury. Conclusion: We report four cases of liver injury, which are possibly related to ingestion of imidacloprid. In management, consideration should be given to repeating liver tests as an outpatient if initial tests are normal, with counseling on the possibility of delayed liver injury.